Impact of Agricultural Credit on Agricultural Production: Evidence from Bangladesh (Social Science Review, 2023)
This article aims to portray the impact of agricultural credit on agricultural production in Bangladesh using the Johansen co-integration method. However, the Johansen co-integration test requires the concerned variables to be in the same order of integration. Augmented Dickey-Fuller (ADF), Phillips Perron (PP), and Kwiatkowski, Phillips, Schmidt and Shin (KPSS) tests have been performed to check whether the variables contain a unit root. ADF, PP, and KPSS tests suggest that all variables- the natural logarithm of agricultural production, agricultural credit, fertiliser use, and agricultural employment- follow the integration of order one. The test results show that credit disbursed in agriculture and fertiliser usage significantly increase agricultural production in the long run. However, our study suggests that agricultural employment has a negative long-run effect on agriculture employment. Regarding post-estimation, we did not find any serial correlation in the Vector Error Correction Model (VECM) model, and residuals of the VECM model are also normally distributed. Our findings suggest that credit disbursed in the agricultural sector facilities needs to be augmented to increase and sustain agricultural output.Social Science Review, Vol. 40(1), Jun 2023 Page 109-128